Products of processing of sunflower seeds in meat products - Strashynskyi, Igor; Shevchenko, Tatiana (My University, 2021)
Increasing the production of protein to meet the needs of the population of Ukraine and the world is one of the most difficult problems of our time and is of paramount practical importance. Despite the achievements of the agro-industrial complex and the achievements of food science, the problem of protein deficiency in the diet still remains unresolved.
Keywords: кафедра технології м’яса і м’ясних продуктів; production of protein; problem of protein deficiency; sunflower seeds